Ash Deposition and Alkali Metal Migration during Zhundong High-alkali Coal Gasification. (May 2017) - Li, Guangyu; Wang, Chang'an; Wang, Pengqian; Du, Yongbo; Liu, Xuan; Chen, Wufeng; Che, Defu
Abstract: Ash deposition is particularly serious during Zhundong coal combustion/gasification due to its high alkali metal content, which causes great troubles and limits its utilization. This paper focuses on the ash deposition characteristics and migration disciplinarian of akali metal during Zhundong coal gasification varing with different conditions, such as ash deposition temperature, gasification temperature, O2 /coal, steam/coal, and deposition time. Experimental result indicates that gasification conditions play a significant role on ash deposition. The root cause of severe fouling is the high content of Na in Zhundong coal, most of which is water-soluble. Besides, the contents of Na, Fe, S, Cl in ash are obviously changed with flue gas temperature increasing, indicating these elements have great influence on ash deposition, and the migration of Na, Fe and Cl presents similar variation during deposition. In addition, Na deposits mainly above 873 K, and Fe gains enrichment in ash at various temperatures. With the increase of gasification temperature, the content of Na in the ash is increased, which could exacerbate ash deposition. Both O2 /coal and steam/coal have a certain influence on migration of elements, and the increases of O2 /coal and steam/coal can relieve the ash fouling phenomena. Deposited ash on heating surface will react with Na in flue gas at high temperature, leading to the increase of content of Na in the ash with deposition time increasing.